Pengaruh Bermain Gymnastic Terhadap Kecerdasan Kinestetik Anak di Taman Kanak Kanak Harniatun Arrazzaq Bandar Lampung - Kuswanto, Cahniyo Wijaya; Tadjuddin, Nilawati; Indriani, Silvi; Pratiwi, Dona Dinda (Institut Agama Islam Negeri Madura, 2024)
Lack of coordination of a person's movements is caused by the lack of optimal kinesthetic intelligence provided from an early age. This research is aimed at stimulating and developing children's kinesthetic intelligence. The type of research used is quantitative research with a Quasi Experimental research method and a Posttest Only Control Design design with the samples used, namely children in classes B1 and B2 consisting of experimental classes and control classes using purposive sampling techniques. The data collection techniques used are observation and documentation. The analysis technique for this research uses the SPPS version 26 for Windows program. Prerequisite test analysis was carried out to calculate normality using the Kolmogorov-Smirnov test, calculating homogeneity using the statistical Lavene test on both samples (Classes B1 and B2) and hypothesis testing analysis using the t test with the Independent sample T-test formula. Based on the results of calculations with the help of the SPPS program using a significance level of 5%, the hypothesis calculation results were obtained with a confidence level of 95%, tcount was 20.259, greater than ttable, namely 2.036 (20.259 > 2.036) with Sig. (2-tailed) of 0.000 where smaller than 0.05 (0.000 < 0.05) means that H0 is rejected and Ha is accepted. The conclusion is that there is an influence of playing gymnastics on children's kinesthetic intelligence at Harniatun Arrazzaq Kindergarten in Bandar Lampung.